Konseling kelompok untuk menurunkan stres selama sekolah daring - Yana Damayanti (Procedia : Studi Kasus dan Intervensi Psikologi, 2022)
During the pandemic, learning at school is delivered by online. Online schools  make many students experience stress due to the burden  of the lessons. During this pandemic the learning methods provided by schools  are more difficult to understand. The purpose of this case study is to reduce the symptoms of stress in students by using group counseling. The assessment method  uses interviews, observation, and the Educational  Stress Scale  for Adolescents (ESSA). The subjects in this case were 5 teenagers aged  13 to 14 years  old. The subjects were junior high school students in class VII and class  VIII. All subjects live together in a boarding  school in Malang. Before the intervention,  the stress level of the subjects was in the high category. After the intervention  with group counseling decreased to a moderate level.